Combustion optimization and NOx reduction of a 600 MWe down-fired boiler by rearrangement of swirl burner and introduction of separated over-fire air. (10th February 2019) - Yang, Wu; Wang, Ben; Lei, Siyuan; Wang, Ke; Chen, Tao; Song, Zijian; Ma, Chuan; Zhou, Yiding; Sun, Lushi
Abstract: In this paper, a 600 MWe Babcock & Wilcox boiler is selected as the research object. Numerical simulation and field experiments have been applied to this study under original and new combustion systems. The new approach mainly involves changing the operation mode of swirl burner, rearranging secondary air, and employing separated over-fire air. Numerical results showed that NOx emissions and the unburned combustible in flue dust decrease with the arrangement of the swirl burner changing from co-rotating mode to counter-rotating one. Consequently, counter-rotating mode of adjacent burners was chosen as the optimized arrangement. The introduction of separated over-fire air resulted in a remarkably reduction of the NOx emissions, which reduced from 1085 mg/m 3 to 547 mg/m 3 . With increase of the distance between separated over-fire air and arch from 0.5 m to 3.0 m, NOx emissions changed slightly and the unburned combustible in flue dust were not greatly affected. When the distance continued increase to 6.0 m, NOx generation was suppressed and boiler efficiency declined. Considering the economic efficiency and NOx emissions reduction, the optimal sofa position is 3.0 m above the arch. In situ measurement results are consistent with the modelling predictions This work provides a feasible and economic approach for Babcock & Wilcox down-fired boilers to achieve high efficiency and low pollutant emissions. Highlights: Study the effects of burner rearrangement on low-nitrogen combustion. Accurate calculate carbon content in fly ash by using CBK model. Optimize the combustion system based on numerical simulations. NOx at furnace exit decrease from 1085 mg/m 3 to 547 mg/m 3 by introduce SOFA.